2014
DOI: 10.2174/1567205011666141001113135
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Oxidative Death of Lymphocytes from Alzheimer Patients Correlates with Dementia Severity

Abstract: We previously reported on enhanced susceptibility to death of lymphocytes from Alzheimer's disease (AD) patients when exposed to hydrogen peroxide (H 2 O 2 )-induced oxidative stress and an increased resistance to death in those of patients with a history of skin cancer. This is consistent with our hypothesis proposing that the cellular machinery controlling cell death is deregulated in opposite directions in Alzheimer's disease (AD) and cancer, to explain the inverse association observed in epidemiological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 46 publications
8
27
1
Order By: Relevance
“…However, AD lymphocytes maintained a significantly increased susceptibility to death inhibition compared with control lymphocytes (Figures 2A,B), as was reported previously (Ponce et al, 2014). An increase in 3-ABA concentration did not modify these results suggesting that the difference was not due to insufficient PARP-1 inhibition (data not shown).…”
Section: Resultssupporting
confidence: 89%
“…However, AD lymphocytes maintained a significantly increased susceptibility to death inhibition compared with control lymphocytes (Figures 2A,B), as was reported previously (Ponce et al, 2014). An increase in 3-ABA concentration did not modify these results suggesting that the difference was not due to insufficient PARP-1 inhibition (data not shown).…”
Section: Resultssupporting
confidence: 89%
“…This is in accordance with increased glutathione disulfide levels and lowered plasma levels of glutathione GSH observed in AD lymphocytes [46]. Furthermore, recent data showed that increased susceptibility to oxidative death of lymphocytes from AD patients correlates with dementia severity [50].…”
Section: Prospective Ad Biomarkers In Lymphocytessupporting
confidence: 81%
“…This is in accordance with increased glutathione disulfide levels and lowered plasma levels of glutathione GSH observed in AD lymphocytes [46]. Furthermore, recent data showed that increased susceptibility to oxidative death of lymphocytes from AD patients correlates with dementia severity [50].An additional molecular change connected to mitochondrial oxidative stress in the brains and lymphoblastoid cells of AD patients is an increased frequency of DNA mutation in mitochondrial DNA (mtDNA) [51]. Numerous such mutations were found in locations of known mtDNA replication and transcription regulatory elements, thus leading to reduced transcript levels of crucial mitochondrial proteins that were deleterious to mitochondrial functions.…”
supporting
confidence: 83%
“…There is evidence showing that oxidative stress pathways are involved in the pathophysiology of AD [4,5]. The disruption of balance between the formation of reactive oxygen species (ROS) and their neutralization leads to the damage of genetic material as well as other biomolecules.…”
Section: Introductionmentioning
confidence: 99%